Cocktail Therapy of Fosthiazate and Cupric-Ammoniun Complex for Citrus Huanglongbing - Duan, Jingwei; Li, Xue; Zhang, Junzhe; Cheng, Baoping; Liu, Shuhan; Li, Hongmei; Zhou, Quan; Chen, Wenli (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is a destructive citrus bacterial disease caused by Candidatus Liberibacter asiaticus (Ca.Las) and cannot be cured by current pesticides. Root lesion and Tylenchulus semipenetrans juveniles were observed in HLB-affected citrus tree roots. We hypothesize that root treatment with fosthiazate (FOS) and Cupric-Ammonium Complex (CAC) will improve the root growth and inhibit HLB. CAC is a broad spectrum fungicide and can promote growth of crops. FOS kills Tylenchulus semipenetrans and protects roots from damage by harmful bacteria such as Ca.Las. After 90 days of combination treatment of FOS and CAC through root drenches, the citrus grew new roots and its leaves changed their color to green. The inhibition rate of Ca.Las reached more than 90%. During treatment process, the chlorophyll content and the root vitality increased 396 and 151%, respectively, and starch accumulation decreased by 88%. Transmission electron microscopy (TEM) and plant tissue dyeing experiments showed that more irregular swollen starch granules existed in the chloroplast thylakoid system of the HLB-infected leaves. This is due to the blocking of their secretory tissue by starch. TEM and flow cytometry experiments in vitro showed the synergistic effects of FOS and CAC. A transcriptome analysis revealed that the treatment induced the differential expression of the genes which involved 103 metabolic pathways. These results suggested that the cocktail treatment of FOS and CAC may effectively kill various pathogens including Ca.Las on citrus root and thus effectively control HLB.